NEK6‐mediated phosphorylation of human TPP1 regulates telomere length through telomerase recruitment. (11th July 2016) - Hirai, Yugo; Tamura, Miki; Otani, Junji; Ishikawa, Fuyuki
Abstract : Shelterin component TPP1 plays critical roles in chromosome end protection and telomere length regulation. Specifically, TPP1 contains an OB‐fold domain that provides an interface to recruit telomerase. However, it remains largely unknown how telomerase recruitment is regulated by cell cycle regulators. We show that TPP1 interacts with the cell cycle regulator kinase NEK6 in human cells. We found that NEK6‐mediated phosphorylation of TPP1 Ser255 in G2/M phase regulates the association between telomerase activity and TPP1. Furthermore, we found evidence that POT1 negatively regulates TPP1 phosphorylation because the level of Ser255 phosphorylation was elevated when telomeres were elongated by a POT1 mutant lacking its OB‐fold domains. Ser255 is located in the intervening region between the telomerase‐recruiting OB‐fold and the POT1 recruitment domains. Ser255 and the surrounding amino acids are conserved among vertebrates. These observations suggest that a region adjacent to the OB‐fold domain of TPP1 is involved in telomere length regulation via telomerase recruitment. Abstract : Human telomere protein TPP1 is phosphorylated in G2/M‐phase cells by NEK6 kinase to regulate telomerase reactions.